Cholangiocytes contribute to hepatocyte regeneration after partial liver injury during growth spurt in zebrafish - Sema Elif Eski; Jiarui Mi; Macarena Pozo-Morales; Gabriel Garnik Hovhannisyan; Camille Perazzolo; Rita Manco; Imane Ez-Zammoury; Dev Barbhaya; Anne Lefort; Frédérick Libert; Federico Marini; Esteban N. Gurzov; et al. (Nature Communications)
Abstract The liver’s regenerative ability depends on injury extent. Minor injuries are repaired by hepatocyte self-duplication, while severe damage triggers cholangiocyte involvement in hepatocyte recovery. This paradigm is well-documented for adult animals but is less explored during rapid growth. We design two partial liver injury models in zebrafish, which were investigated during growth spurts: 1) partial ablation, killing half the hepatocytes; and 2) partial hepatectomy, removing half a liver lobe. In both injuries, de novo hepatocytes emerged alongside existing ones. Single-cell transcriptomics and lineage tracing with Cre-driver lines generated by genome editing identified cholangiocytes as the source of de novo hepatocytes. We further identify active mTORC1 signalling in the uninjured liver of growing animal to be a regulator of the enhanced plasticity of cholangiocytes. Our study suggests cholangiocyte-to-hepatocyte transdifferentiation as the primary mechanism of liver regeneration during periods of rapid growth.